PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE PERUSAHAAN MELALUI EMPLOYEE ENGAGEMENT DAN JOB SATISFACTION SEBAGAI INTERVENING VARIABLE PADA PERUSAHAAN RETAIL TERBUKA DI SURABAYA - Linata, Sugiharto (Business Accounting Review, 2015)
Â The purposes of this research was to know the positive and significant influence of transformational leadership towards financial performance; job satisfaction towards financial performance; and employee engagement towards financial performance in retail companies in Surabaya. The data analysis technique used was Partial Least Square (PLS) with the calculation process assisted by SmartPLS software application program to process the data of the questionnaires. The results showed there were negative and significant influence of transformational leadership towards financial performance; there were positive and insignificant influence of job satisfaction towards financial performance; and there were positive and significant influence of employee engagement towards financial performance in retail companies in Surabaya, and there was also the indirect influence of transformational leadership towards financial performance through job satisfaction and employee engagement.